Obesity incidence is related to month of birth - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: The relationship between the month of birth and obesity status of individuals has been claimed but not proven convincingly. We aim to provide more evidence towards the presumed relationship between month of birth and physical characteristics of individuals. Materials and Methods: We used a Bio-impedance device to determine physical characteristics of 3,000 informed volunteers who attended our clinic. Results: We found that the individuals who were born in the first three months of the year were heavier, taller and older than the applicants who were born in later months of the year. Conclusion: We can conclude that the month of birth was significantly related to obesity incidence. We believe that this information will add to the knowledge on the importance of the relationship between birth month and physical and health characteristics of individuals living in a country with extreme seasonal temperatures.
Keywords: Body mass index; Weight; Fat content; Season; WEIGHT; HEIGHT; SCHOOLCHILDREN; BORN